Identification of context-workflow dependencies in knowledge-intensive business processes using log analysis - Левыкин, Виктор Макарович; Чалая, Оксана Викторовна (Technology audit and production reserves, 2016)
Multivariate knowledge-intensive business processes that change at runtime on the basis of knowledge are considered. For more effective implementation of the process performers correct the course of its action with the help of their personal knowledge and experience. The dependencies that reflect the link between the execution context of the process actions are used. To improve the process control efficiency it is necessary to formalize the context-sensitive knowledge of artists and include them in the process model. Context states, as well as the sequence of process actions are recorded in the log of information system. This presents an opportunity to highlight the links between the context and the process based on log analysis. The method of selection of context-procedural dependencies of knowledge-intensive business process is proposed. This process involves the identification of repetitive sequences of events that reflect the process execution, as well as state of context artifacts and the relationships between artifacts that lead to the implementation of these actions. The method improves the efficiency of process control of knowledge-intensive business processes by supplementing the process mode by identifying dependencies.